2013
DOI: 10.1088/1748-6041/8/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Degrading magnesium screws ZEK100: biomechanical testing, degradation analysis and soft-tissue biocompatibility in a rabbit model

Abstract: Magnesium alloys are promising implant materials for use in orthopaedic applications. In the present study, screws made of the Mg-alloy ZEK100 (n = 12) were implanted in rabbit tibiae for four and six weeks, respectively. For degradation analysis, in vivo µ-computed tomography (µCT), a determination of the weight changes and SEM/EDX examinations of the screws were performed. Screw retention forces were verified by uniaxial pull-out tests. Additionally, soft-tissue biocompatibility was estimated using routine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 56 publications
0
37
1
Order By: Relevance
“…Based on histological data and from implant pull out forces, bone conductive properties of magnesium alloy implants were observed and proposed to be mediated by magnesium hydroxides as well as by calcium phosphates present in the magnesium corrosion layer [17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on histological data and from implant pull out forces, bone conductive properties of magnesium alloy implants were observed and proposed to be mediated by magnesium hydroxides as well as by calcium phosphates present in the magnesium corrosion layer [17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…The gas pockets around implantable devices were observed in human patients 14 as well as animal models. 17,19,48,49 Several papers studied the effects of surface modifications on the gas pocket formation. Fischerauer et al observed decrease in the gas pocket formation in the 1st 2 weeks postimplantation with the implants treated by micro-arc oxidation, however these differences were not significant and at weeks 3 and 4 the gas volume was higher than in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 146,199 ] The accelerated corrosion behavior of Mg and its alloys, in accordance with an early loss of integrity and a high hydrogen evolution rate, has been proven in various in vivo studies. [ 21,35,[200][201][202] A lower and upper limit for the corrosion rate of degradable suture implants is currently not defi ned. Surface treatments, especially coatings, are currently under extensive investigation to delay corrosion and to provide an increased implant endurance.…”
Section: Reviewmentioning
confidence: 99%